Seventh-Day Adventist Historiography: A Work in Progress - Butler, Jonathan M. (Church history, 2018)
In the past decade, Seventh-day Adventist (SDA) historiography has enjoyed an efflorescence that warrants the attention of church historians. Two notable books mark the surge of interest in Adventism and its prophet: one of them an extraordinary denominational history, Seeking a Sanctuary: Seventh-day Adventism and the American Dream, by Malcolm Bull and Keith Lockhart (1989; 2007); the other an excellent collection of essays, Ellen Harmon White: American Prophet, edited by Terrie Dopp Aamodt, Gary Land, and Ronald L. Numbers (2014). Both books remind church historians that Seventh-day Adventism deserves its due as one of America's original religions. Since 2005, however, a number of books have appeared that understandably have received less scrutiny. The Adventist Pioneer Series, in particular, produced by SDA scholars and published by SDA presses, has largely escaped the notice of the wider, non-SDA historical community. This is unfortunate. There is the inevitable unevenness among these volumes, and given their intent to serve a popular Adventist audience, there is also the predictable parochialism in them, in some more than others. Nevertheless, to date there are several books in the series, and no doubt more to follow, which should command serious scholarly interest. To make our way through this largely unfamiliar historiographical landscape calls for a little mapping. Most of these authors come from SDA backgrounds, whatever distance they have gone from them. It will be necessary, then, to reflect on the differences between a historian of Adventism and an Adventist historian, secular versus supernatural history, and apologists who rate scholarly notice and those who do not. It will be important as well to realize that there is no hard, unyielding line between these differences.